The States Position regarding Registration of Customary Land (Orientasi Negara dalam Pendaftaran Tanah Adat di Indonesia) - Simarmata, Rikardo (The Indonesian Journal of Socio-Legal Studies, 2021)
Indonesian Agrarian Law syncretically aims to create a national legal unity and respecting customary rights to land at the same time. The second aim is to tolerate the diversity in national land law. In the implementation of customary land registration, these two objectives do not appear to be in sync. In fact, the first objective is very important, which causes the second goal to receive very little attention. This paper sees that the process of customary land registration shows the tensions in achieving these two objectives. The paper will explain how the Indonesian government subordinates the second objective. In fact, the first objective has become the orientations when it comes to the registration of customary land, as well as the regulations and practices supporting it. Such orientations, regulations, and practices cause many consequences for the communalistic nature of ulayat lands, as well as the law implementation and authority of the lands